development of user interface design on isoplus city run website - Evita Sekar Arum; Dewiyani Sunarto M.J; Tri Sagirani; Puspita Kartikasari (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Isoplus city ran has one of activity that is running race called isoplus city run at isopluscityrun.com. as long as the website has been implemented, there are 71,3% users that have accessed through a desktop device. there are some problems encountered by users, one of them is users cannot fully get and understand the information like the features and some of contents are too much to comprehend, so incompatible to be accessed with other deviecs. the solution is to develop a user interface at isoplus it run's website using heuristic evaluation methode and find the mistakes also to evaluate the successness of the website. The results of data processing show the level of problem improvement with high priority on the variable user control and freedom, namely assistance when the website error and the number of clicks and the problems in the aesthetic and minimalist design variables are incomplete information. The results of the design development by considering the initial design of the website and the results of the data processing of respondents. The final step is evaluated by the respondents using the heuristics evaluation method, from the ten variables average value obtained is 1.2 from the range of saverity rating value of 1 to 5, the value of 1 is that there is no problem which means the results of the design development that has been done has the level of problem in the category there is no problem in usability. The final results obtained recommendations in form of user interface design in accordance with the needs of the isoplus city run in supporting activities.